ANALISIS PENGARUH KUALITAS PELAYANAN,HARGA DAN PROMOSI TERHADAP KEPUASAN PELANGGAN - Mubasyiroh, Iffatin; Nasution, Ute Chairuz; Pujianto, Agung (Jurnal Dinamika Administrasi Bisnis, 2018)
This study entitled â€œAnalysis of influence of service quality, price, and promotion to customer satisfaction (case study at CV. Fastprint Indonesia, Jl. Manyar kertoarjo VII no 36 Surabaya)â€ this research aims to influence the influence of service quality, price and promotion satisfaction and to know the dominant influence among service quality, price and promotion in CV. Fastprint Indonesia in January 2018.Â Â Â Â Â Â Â Â Â Â Â  Collecting data using questionnaires with sampling technique non probability sampling is incidental sampling that the number of respondents 100 people. The method of data analysis is multiple linear regression analysis which is processed with the help of IBM SPSS 22 application. Variables used are service quality, price and promotion as independent variable and customer satisfaction as dependent variable. Â Â Â Â Â Â Â Â Â Â Â  The results of research indicate that the influence of customer satisfaction on service quality, price and promotion that simultaneously effect. This can be shown with the value of F = 55,615, sig 0,000 and R2 value of 0,623 which means 62,3% customer satisfaction is explained by the service quality, price and promotion while 37,7% is explained by other variables not examined in this study.Keywords : service quality, price, promotion, customer satisfaction